Surface markers: An identity card of endothelial cells. (12th September 2019) - Ribatti, Domenico; Tamma, Roberto; Ruggieri, Simona; Annese, Tiziana; Crivellato, Enrico
Abstract: All endothelial cells have the common characteristic that they line the vessels of the blood circulatory system. However, endothelial cells display a large degree of heterogeneity in the function of their location in the vascular tree. In this article, we have summarized the expression patterns of a number of well‐accepted endothelial surface markers present in normal microvascular endothelial cells, arterial and venous endothelial cells, lymphatic endothelial cells, tumor endothelial cells, and endothelial precursor cells.